Some Results on N-Tupled Coincidence and Fixed Points of Graphs on Metric Spaces and an Application to Integral Equations. (5th November 2018) - Soliman, Ahmed H.; Nabil, Tamer
Abstract : In this work, we establish some N-tupled common coincidence and N-tupled common fixed points for the mappings satisfying a( φ - ψ ) - type contractive condition in a complete metric space endowed with a directed graph (for short digraph). Also, we apply our theoretical results to study the existence and uniqueness of solutions for systems of integral equations.